EFFECT OF PROJECT TEACHING METHOD ON STUDENTS’ ACADEMIC ACHIEVEMENT IN BUILDING/WOODWORK TRADE IN OYO STATE GOVERNMENT TECHNICAL COLLEGES (NAU Journal of Technology and Vocational Education, 2024)
Poor academic achievement of students in building/woodwork trade in Oyo Stategovernment technical colleges as a result of defects in demonstration method ofteaching prompted the researchers to adopt project method as an alternative means toeffective teaching and a way of replacing the old one. Two research questions andtwo hypotheses were postulated in line with the stated objectives. Quasi-experimentalresearch design was adopted for the study. A sample of 78 building/woodwork tradeyear III students drawn by purposive sampling technique from a population of 250students in five government technical colleges was used for the study. The instrumentfor data collection was a Building/Woodwork Trade Achievement Test (BWTAT)validated by three experts. Test-retest method was used to obtained reliabilitycoefficient value of 0.76 through Person product moment correlation coefficient. Thestudy revealed that project teaching method was more effective than conventionalmethod in enhancing students’ academic achievement in building/ woodwork trade.Also, it was found that project teaching method increases male academic achievementthan female students in building/woodwork trade. Therefore, it was recommended thattechnical teachers should have workshop guidelines on how to use project method forpractical skills on students. Also, technical teachers should ensure they plan theirlessons with equal learning chances for both male and female students.
Keywords: Project Teaching Method, Academic Achievement, Building/Woodwork Tradeand Government Technical Colleges.